1998
DOI: 10.1038/sj.ijo.0800603
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diet and physical activity affect the body mass index of Chinese adults

Abstract: OBJECTIVE: To examine the relationship between diet, particularly dietary fat intake, and body mass index (BMI). DESIGN: Prospective study of adults who participated in the 1989 and 1991 China Health and Nutrition Survey. SUBJECTS: 3484 adults aged 20±45 at baseline (1989) survey. MEASUREMENTS: Measurement of dietary intake with replicated 24 h dietary recalls. Anthropometric measurements. Measurements of physical activity, smoking habit and socio-economic factors. RESULTS: Change in fat intake was positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
4
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 18 publications
10
114
4
3
Order By: Relevance
“…This pattern is consistent with earlier research examining overweight trends for Chinese children (1991-1997) and adults (1989-2000) (Wang et al, 2002(Wang et al, , 2006a. The pattern is contrary to trend data from the 1980s showing increased overweight among Chinese women Paeratakul et al, 1998;Wang et al, 2006a). Explanations for the shift may be linked to an increasing desire for slimness among Chinese women or a preference given to males when allocating household resources (Lee, 1993;Lee et al, 1996;Lee and Lee, 2000;Luo et al, 2001;Fung and Yuen, 2003).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This pattern is consistent with earlier research examining overweight trends for Chinese children (1991-1997) and adults (1989-2000) (Wang et al, 2002(Wang et al, , 2006a. The pattern is contrary to trend data from the 1980s showing increased overweight among Chinese women Paeratakul et al, 1998;Wang et al, 2006a). Explanations for the shift may be linked to an increasing desire for slimness among Chinese women or a preference given to males when allocating household resources (Lee, 1993;Lee et al, 1996;Lee and Lee, 2000;Luo et al, 2001;Fung and Yuen, 2003).…”
Section: Discussionsupporting
confidence: 85%
“…Varying patterns of change in weight status for Chinese children and adults are hypothesized to be influenced by biological differences in adults and children, variations in how children and adults are affected by environmental change and possible interaction between biological and environmental factors . Increases in the overweight prevalence among adults have been linked with decreases in work-and transport-related physical activity, while a relationship between overweight and a high-fat, low-fiber diet has been found for both children and adults (Paeratakul et al, 1998;Bell et al, 2001Bell et al, , 2002Wang et al, 2003). More research is needed in order to better understand the relationship between weight status changes for children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Given the enormous heterogeneity in activities within a narrow occupation, this provides a much more precise measure of energy expenditures at work than a classical measure of occupation. While formal reliability and validity analyses have not been run on this variable, several published studies have found it to be a more significant predictor of weight than classical measures of occupation (Bell, Ge, & Popkin, 2001;Paeratakul, Popkin, Ge, Adair, & Stevens, 1998;Stookey, Adair, Stevens, & Popkin, 2001). Further, it is closely related to several survey instruments which have been shown to have good reliability and validity in diverse populations (Ainsworth, Richardson, Jacobs, Leon, & Sternfeld, 1999;Baecke, Burema, & Frijters, 1982;Philippaerts & Lefevre, 1998;Reis, Dubose, Ainsworth, Macera, & Yore, 2005).…”
Section: Dependent Variablementioning
confidence: 99%
“…During a detailed interview, respondents were asked about the time spent sitting, standing, walking and lifting heavy loads during an average working day, and then were categorized as having light, moderate or heavy occupational activity. While formal reliability and validity analyses have not been run on this variable, several published studies have found it to be a significant predictor of weight (Paeratakul et al, 1998;Bell et al, 2001;Stookey et al, 2001). Further, it is closely related to several survey instruments, which have been shown to have good reliability and validity in diverse populations (Baecke et al, 1982;Philippaerts and Lefevre, 1998;Ainsworth et al, 1999;Reis et al, 2005).…”
Section: Study Variablesmentioning
confidence: 99%